2009
DOI: 10.4319/lo.2009.54.3.0869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Saharan dust inputs on bacterial activity and community composition in Mediterranean lakes and reservoirs

Abstract: We assessed the effects of Saharan dust inputs of particulate matter (PM), total phosphorus (TP), total nitrogen, and water soluble organic carbon (WSOC) on bacterial abundance (BA) in two alpine lakes and two reservoirs in the Mediterranean region. We also experimentally assessed the effects of dust inputs on bacterial activity and community composition and explored the presence of airborne bacteria. We found synchronous BA dynamics at least in one of the study years for each corresponding pair of ecosystems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
125
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(133 citation statements)
references
References 48 publications
6
125
1
1
Order By: Relevance
“…Atmospheric depositions are the main source of reactive nitrogen in remote mountain catchments (Catalan et al, 1994), particularly ammonium with concentrations in the rain up to 30fold higher than mean values measured in the lake water . High influence of airborne dust nutrients has also been reported Reche et al, 2009) that may fuel AOA nitrification activity. These results reflect the wide set of ecological and thermal conditions where AOA are distributed, ranging from hot springs (Zhang et al, 2008) to the ice layers reported here.…”
Section: Discussionmentioning
confidence: 99%
“…Atmospheric depositions are the main source of reactive nitrogen in remote mountain catchments (Catalan et al, 1994), particularly ammonium with concentrations in the rain up to 30fold higher than mean values measured in the lake water . High influence of airborne dust nutrients has also been reported Reche et al, 2009) that may fuel AOA nitrification activity. These results reflect the wide set of ecological and thermal conditions where AOA are distributed, ranging from hot springs (Zhang et al, 2008) to the ice layers reported here.…”
Section: Discussionmentioning
confidence: 99%
“…In arid regions of the western US and southern Europe, dust emissions can result in substantial nutrient subsidies in the form of Fe, P, and N Lawrence and Neff, 2009;Ballantyne et al, 2011;Reche et al, 2009). Given phosphorus (P) limitation or co-limitation in many alpine areas (Elser et al, 2009;King et al, 2008), dust-derived and other atmospheric P inputs may be especially important.…”
Section: N Mladenov Et Al: Atmospheric Deposition As a Source Of Camentioning
confidence: 99%
“…Alpert et al, 1998;Chaboureau et al, 2011); radiative budget and climate (e.g. Nabat et al, 2012Nabat et al, , 2015a; precipitation chemistry (Chester et al, 1996;Loÿe-Pilot et al, 1986;Avila and Rodà, 2002); soil formation (Nihlén et al, 1995); and biogeochemistry of forest ecosystems (Avila and Peñuelas, 1999), oligotrophic lakes (Morales-Baquero et al, 2006;Reche et al, 2009), and marine surface waters (Guerzoni et al, 1999;Herut et al, 1999;Guieu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%